Measurement of T-Lymphocyte Responses in Whole-Blood Cultures Using Newly Synthesized DNA and ATP - Sottong, P. R. (American Society for Microbiology, 2000)
The proliferative response is most frequently determined by estimating the amount of [(3)H]thymidine incorporated into newly synthesized DNA. The [(3)H]thymidine procedure requires the use of radioisotopes as well as lengthy periods of incubation (>72 h). An alternative method of assessing T-lymphocyte activation in whole-blood cultures involves the measurement of the nucleotide ATP instead of [(3)H]thymidine incorporation. In addition, the Luminetics assay of T-cell activation measures specific T-lymphocyte subset responses through the use of paramagnetic particles coated with monoclonal antibodies against CD antigens. This assay permits rapid (24 h) analysis of lymphocyte subset activation responses to mitogens and recall antigens in small amounts of blood.